PENGARUH TEKNIK MIND MAPPING TERHADAP PENINGKATAN HASIL BELAJAR SISWA MATERI PERPINDAHAN KALOR DI SMP - Marini, Syinta; Tandililing, Edy; Oktavianty, Erwina (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis purpose of this study is to know the influences of mind mapping technique on improving student learning outcomes in materials of heat transfer in grade VII. The form of study used quasi experimental with quasi experimental with nonequivalent control group design. Instrument data collection used in this study involved pretest and posttest that each of them question multiple choice amounted 18 to quantify of learning achievement . The technique of selecting sample used intac group.study uses classes that are composed of control classes and experiment each class consists of 40 students. The result of this study indicate that there is an increase in learning outcomes using mind mapping technique with student using conventional record technique then obtained the result P Value 1.88461 X 10-22< alpha 0.05. Based on the result of this study can be recommended that techniq mind mapping can be use as an alternative learning technique to increase student learning achievement.Keywords: technique, mind mapping, learning outcomes, heat transfer